Réponses

2013-05-06T22:05:03+02:00

E=(4x-3)^{2}+6x(4-x)-(x^{2}+9)\\ E=16x^{2}-24x+9+24x-6x^{2}-x^{2}-9\\ E=9x^{2}\\ \\

 

Le carré de 3x est bien 9x² ! 

 

On a : 

 

E=144=9x²

on cherche donc : 

 

9x²=144

x²=144/9

x²=16

x=4         ou     x=-4

 

E=9x²

E=(\frac{(\sqrt{3})}{3})^{2}*9\\ E=\frac{3}{9}*9\\ E=3\\

 

Voila ! 

 

2013-05-06T22:05:55+02:00

E = (4x-3)²+6x(4-x)-x²-9 

E = 16x² -24x +9 +24x -6x² -x² -9

E = 9x²

E = (3x)² 

 

E = 144

9x² = 144

x² = 144/9 = 16

x = V16 = 4 ou x = -4

 

pour x = (V3)/3

E = 9 * [ (V3) / 3 ) ] ²

E = (9*3) / 9 

E = 3